Differential determinants of gender participation in recreational activities among academic staff of University of Ilorin, Nigeria - Tunde, Afolabi Monisola (Penerbit Universiti Kebangsaan Malaysia, 2019)
Recreational activities can be seen as any activities performed willingly to improve both physical and mental well-being of an individual. This study examines the differential determinants of gender participation in recreational activities among members of academic staff of university of Ilorin, Nigeria. Seventy-four male and seventy female academic members of staff were sampled randomly across all the faculties in the institution. A total number of 148 copies of questionnaire were administered on the sampled respondents. Percentages, tables, factor analysis and Analysis of Variance (ANOVA) were used to analyze the gathered data. Findings revealed that there are 1,117males and 361 females as at January, 2018. Factor 1 (Age) explains the highest percentage of the total variance, followed by Factor 2 (Gender), 3 (academic qualification) and Factor 4 (Employment). Whereas Factor 5 (Accessibility to recreational facilities) explains the lowest percentages of the total variance. The study concluded that awareness should be created for academic members of staff to participate in recreational activities using different recreational facilities available within and outside the institution. This will enhance the physical and psychological wellbeing, thus improving their efficiency.